Integrated Detection of Respiration and Heartbeat With Communication Capabilities Using OFDM-LFM-MP Signals - Zhaoshen Dong; Yan Liu; Yukai Ouyang (IEEE Access)
To address the evolving demands of intelligent networks, integrated sensing and communication (ISAC) has emerged as a focal area of research. This encompasses innovative signal design, radar-based and communication hardware integration, and other vital directions. In particular, Linear Frequency Modulated (LFM) signals have shown considerable promise in contactless health monitoring applications. This paper presents an integrated radar system design leveraging Orthogonal Frequency Division Multiplexing (OFDM) LFM signals, emphasizing the dual capabilities of communication and sensing. Compared to traditional radar signals, the proposed design enhances information transmission without sacrificing sensing performance. Initially, we developed an OFDM-LFM-MP signal by utilizing M-sequences with strong auto-correlation properties for coding communication data. Subsequently, we conduct MATLAB simulations to evaluate the sensing efficacy of the OFDM-LFM-MP signal in detecting heartbeats and respiration alongside its communication performance. Theoretical analyses and simulation outcomes demonstrate that the proposed radar-based integration design significantly improves the detection of heartbeat and respiration while effectively transmitting high-rate information at a signal-to-noise ratio (SNR) exceeding $20~dB$ .